Private antitrust enforcement: a new era for collective redress? - Pais, Sofia Oliveira (2016)
It will be argued in this article that the EU Recommendation on common principles for collective redress might have limited impact on the field of competition law due to: several uncertainties regarding the legal standing in class actions; difficulties in their funding; and the risk of forum shopping with cross-border actions. Nevertheless, Belgium and Great Britain have recently introduced class actions into their national legal systems and addressed some of the difficulties which other Member States were experiencing already. It will also be suggested that the Portuguese model – the ‘Popular Action’ – and recent Portuguese practice may be considered an interesting example to follow in order to overcome some of the identified obstacles to private antitrust enforcement.